Putting the individual in context: paths, capitals and topologies of learning. (1st March 2014) - Faulconbridge, James
Abstract : James Faulconbridge is Professor of Transnational Management at Lancaster University. His research focuses upon the globalisation of professional service firms. Recent articles have examined the nature of stretched communities of learning in such firms, and institutional effects on globalising firms. He is co-author of The Globalisation of Advertising and editor of International Business Travel in the Global Economy .